2019
DOI: 10.1055/a-0889-6132
|View full text |Cite
|
Sign up to set email alerts
|

Quercus ilex Extract Ameliorates Acute TNBS-Induced Colitis in Rats

Abstract: Quercus ilex L. (Fagaceae) is one of the most commonly used plants in folk medicine in the Mediterranean region to treat gastrointestinal disorders. The aim of the present study was to evaluate the effects of a polyphenol extract from mature leaves of Q. ilex on acute 2,4,6-trinitrobenzene sulfonic acid-induced colitis in rats. A polyphenol extract from mature leaves of Q. ilex (250 and 500 mg/kg/day) was administered by gavage 48, 24, and 1 h prior to the induction of colitis with 2,4,6-trinitrobenzene sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In vitro, HT promoted Nrf2 nuclear localization in RAW264.7 macrophages [53]. In vivo, OLE increased Nrf2 protein expression [158,159] while reducing the expression of Nrf2-regulated gene heme oxygenase-1 (HO-1, an antioxidant defense marker) [96,160,161]. Similarly, in vivo, HT augmented Nrf2 expression and transactivation [32,87,150,157,159,[162][163][164].…”
Section: Production Of Radical and Non-radical Ros-like Superoxide An...mentioning
confidence: 99%
“…In vitro, HT promoted Nrf2 nuclear localization in RAW264.7 macrophages [53]. In vivo, OLE increased Nrf2 protein expression [158,159] while reducing the expression of Nrf2-regulated gene heme oxygenase-1 (HO-1, an antioxidant defense marker) [96,160,161]. Similarly, in vivo, HT augmented Nrf2 expression and transactivation [32,87,150,157,159,[162][163][164].…”
Section: Production Of Radical and Non-radical Ros-like Superoxide An...mentioning
confidence: 99%
“…Recently, Castejón et al showed that Quercus ilex improves TNBS-induced colitis via MAPKs/NF- κ B inhibition and Nrf2/HO-1 activation signaling pathways. This in return results in reducing the production of Th1 proinflammatory cytokines and COX-2 and iNOS overexpression [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Castejón et al [ 36 ] studied a trinitrobenzene sulfonic acid (TNBS)-induced Wistar mice model of colitis to evaluate the effects of Quercus ilex L. leaf polyphenolic extract in the activation of the Nrf2 signaling pathway. Before treatment, the mice presented elevated anorexia, intestinal adhesions to adjacent organs, weight/length ratio of the colon, transmural necrosis, edema, diffuse inflammatory cells infiltration, ulceration, and crypt distortion, as well as diminished body weight.…”
Section: Medicinal Plants That Target Nrf2 Pathwaysmentioning
confidence: 99%